Law No. 68 of the year 2016 On Amending Some Provisions of Law No. 453 of the year 1954 Concerning Industrial and Trading Shops and Other Rest-Disturbing, Health-Detrimental and Dangerous Shops = قانون رقم 68 لسنة 2016 بتعديل بعض أحكام القانون رقم 453 لسنة 1954 فى شأن المحال الصناعية والتجارية وغيرها من المحال المقلقة للراحة والمضرة بالصحة والخطرة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic